A systematic review of interventions aiming to promote positive body image in children and adolescents. (September 2022) - Guest, Ella; Zucchelli, Fabio; Costa, Bruna; Bhatia, Radhika; Halliwell, Emma; Harcourt, Diana
Abstract: Evidence shows interventions can improve positive body image in adult women. This systematic review examined the evidence of efficacy of interventions that aimed to increase positive body image in children and young people aged under 18 years. The authors followed PRISMA guidelines for the review. Searches of CINAHL Plus, Medline, PsychINFO, Wiley Online Library, SCOPUS and grey literature were conducted up to February 2021 and identified 4171 papers. Thirteen studies evaluating 12 interventions, designed for children/adolescents aged 9–18 years, were eligible and evaluated using the Effective Public Health Practice Project (EPHPP) Quality Assessment Tool. The studies evaluated body appreciation, body-esteem, and embodiment. Studies using cognitive dissonance, peer support, and psychoeducation had evidence of improving body appreciation and body-esteem in adolescent girls. However, evidence of efficacy for younger children and boys was lacking and the studies ranged in methodological quality. Further research should rigorously evaluate positive body image interventions using second-generation measures that assess specific components of positive body image and consider how to promote positive body image in young children and boys. Highlights: Positive body image interventions for children and young people were evaluated. Thirteen studies evaluating 12 interventions were eligible for the review. Strong and moderate quality studies showed evidence of efficacy. Evidence of efficacy was found with samples of adolescent girls. Psychoeducation, peer support, and cognitive dissonance were effective.